2013
DOI: 10.1088/0029-5515/53/9/093001
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of edge impurity transport with ECRH in the HL-2A tokamak

Abstract: Edge impurity transport is studied in electron cyclotron resonance heating (ECRH) L-mode plasmas of the HL-2A tokamak based on space-resolved vacuum ultraviolet spectroscopy with which radial profiles of impurity line emissions are measured from the core region inside the last closed flux surface (LCFS) and the edge region in the scrape-off layer, simultaneously. The radial profile of carbon emissions of C V (2271 Å: 1s2s 3 S-1s2p 3 P) reconstructed into the local emissivity profile is analysed with a one-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…In contrast, the temperature gradient of the main ions has stabilizing and destabilizing effects in the regions of R/L nz <130 and R/L nz >130, respectively, and, therefore, raises the threshold in NIDG case (see the light blue curve for 0.2 i h = versus the red curve for 0 i h = in figure 19(c) Considering the parameters R/L nz = 25 and f z =0.3, such a reversion occurs at R/L nz >83. Nevertheless, more numerical results demonstrate that such a reversion is not necessary for the instability to occur, although reversed profiles of main ions have been observed in the periphery of HL-2A, TJ-II and RFXmod plasmas [28,32,50,51].…”
Section: Impurity Modementioning
confidence: 94%
“…In contrast, the temperature gradient of the main ions has stabilizing and destabilizing effects in the regions of R/L nz <130 and R/L nz >130, respectively, and, therefore, raises the threshold in NIDG case (see the light blue curve for 0.2 i h = versus the red curve for 0 i h = in figure 19(c) Considering the parameters R/L nz = 25 and f z =0.3, such a reversion occurs at R/L nz >83. Nevertheless, more numerical results demonstrate that such a reversion is not necessary for the instability to occur, although reversed profiles of main ions have been observed in the periphery of HL-2A, TJ-II and RFXmod plasmas [28,32,50,51].…”
Section: Impurity Modementioning
confidence: 94%
“…The independent transport coefficients can be obtained when more than three successive lines are used to compare with simulated results. In a similar study of ECRH effects on carbon at HL-2A (Cui et al 2013), the same method showed that as few as two successive emission lines are needed to determine ν and D if additional constraints are taken into account on the radial profiles and impurity sources.…”
Section: One-dimensional Modelling With Strahlmentioning
confidence: 99%
“…Core impurity transport in the outer half of the plasma radius is studied in low-density ECH discharges (2 × 10 13 cm −3 ) of HL-2A [38]. A ratio of CV to CIV indicating an index of the core impurity transport between LCFS (last closed flux surface) and a radial region of the CV emission, e.g.…”
Section: Core Impurity Transportmentioning
confidence: 99%